Real-World Ethical Dilemmas in Laboratory Safety for Microbiology Under-Resourced and Outreach Teaching - Smith-Keiling, Beverly L. (Frontiers in Microbiology, 2021)
With modernization of safety standards for microbiology outreach teaching laboratories, ethical challenges arise in teaching microbiology for the public good without short-changing students in under-resourced situations, or when institutional support is subpar. Still, educators want students to engage in applied skills for inquiry, research-based microbial learning activities—safely. Following several U.S. microbial outbreaks, federal investigation traced sources back to teaching laboratories. Policy discussions ensued. The American Society for Microbiology (ASM) Task Force provides recommended but not mandated guidelines; however, guidelines are not amenable by all. Here, a real-world, ethical scenario of a university-level outreach microbiology laboratory course hosted at several locations provides context for under-resourced challenges in safety compliance. In this example of biomedical and public health ethical considerations, upper administration puts the onus on instructors to assure safe labs for their students and the general public. Temporarily hired instructors without curriculum or sufficient institutional support are put in precarious positions with often egregious practices to get the job done. This scenario is examined with different public health ethical frameworks and principles: non-maleficence, beneficence, health maximization, efficiency of policy regulations, respect for institutional and instructor autonomy, justice, and proportionality balancing stakeholder concerns. Sample curricular strategies are employed to mitigate these challenges. Taking a utilitarianism framework of the greatest good for the most benefit, this paper advocates for social justice supporting access to education as a moral duty. Administrations should ensure instructors are supported sufficiently to provide safe, authentic learning experiences. Solutions for under-resourced outreach teaching are needed for public trust.